UPAYA PENINGKATAN MINAT BACA DAN KEPUASAN PENGUNJUNG PERPUSTAKAAN MODERN SULAWESI TENGGARA - Buana, Tenri; Mulyadi, Edi; Hardian, Dafyar Eliadi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study aims to thoroughly examine the efforts to enhance reading interest and visitor satisfaction at the Modern Library of Southeast Sulawesi. Employing a qualitative descriptive approach, this research explores the perceptions and experiences of informants, including the library head as the key informant, library staff as main informants, and visitors as supporting informants. Data were collected through in-depth interviews, direct field observations, and documentation of the library’s facilities and activities. The data were analyzed using the Miles and Huberman model, encompassing data reduction, data display, and systematic verification of conclusions. The findings reveal that the modernization of library facilities, including the provision of comfortable reading spaces and technological amenities such as free Wi-Fi access, are dominant factors encouraging increased reading interest, particularly among students and university attendees. Furthermore, professional and friendly staff services contribute positively to visitor satisfaction. Nevertheless, this study identifies challenges such as the limited availability of the latest book collections and suboptimal promotion of literacy programs, which impact the library’s ability to reach a broader audience. The study recommends that library management regularly update the collection, enhance human resource capacity through training, and strengthen communication and promotion strategies to maximize the library’s impact on the literacy culture in Southeast Sulawesi. Keywords: Reading Interest, Visitor Satisfaction, Modern Library, Public Service, Literacy, Library Management